PENINGKATAN KEBUTUHAN PSIKOLOGIS ANAK-ANAK PANTI ASUHAN SINAR DAMAI SEJAHTERA MELALUI MINI GAMES - Sinaga, Mutiara Annisa; Ginting, Natalia Geovany; Sipayung, Roh Binardo; Lumbantobing, Roseva Ayu; Adawiyah, Putri Syahrani; Ritonga, Fajar Utama (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
An orphanage is a social welfare institution that has the responsibility to provide social welfare services to a derelict child by providing help and eradicating the derelict child, providing physical, mental, and social welfare alternate services in custody so that they acquire broad, appropriate, and adequate opportunities for their personality development according to the expected as part of the next generation of the nation's ideals and as people who will participate in the active field of national development. Project Based Learning or field practice is conducted at Sinar Damai Sejahtera Orphanage for 3 weeks. The purpose of this research is to conduct mini-research and mini-projects related to the service system at Sinar Damai Sejahtera Orphanage. The result of the research describes the process of using the main method of social group work through the phases of intervention generally which consist of engagement, intake, contract, assessment, planning, implementation, and termination on the intervention level of the mezzo (small group) and the social service system at Sinar Damai Sejahtera Orphanage. In the program's implementation, the form of contribution or contribution from the researchers is making and carrying out mini-games and providing groceries to Sinar Damai Sejahtera Orphanage.